The vulnerable patient: Refocusing on the plaque? - Eijgelaar, Wouter J.; Heeneman, Sylvia; Daemen, Mat J. A. P. (Thrombosis and Haemostasis, 2009)
The term ‘vulnerable plaque’ is used to refer to the lesions that are prone to rupture and may cause life-threatening events like acute coronary syndrome or stroke.The study of the vulnerable plaque phenotype and its detection has attracted increasing interest over the past decades. During this time, there have been some remarkable transitions in the paradigm on methods to identify patients at risk or patients to treat.Whereas formerly, the key factors used to determine an individual’s risk were primarily population-based traditional risk factors such as age, sex, body mass index, hypertension etc., new approaches are based on conditional risk factors that represent an individual’s current risk of suffering a cardiovascular event.These population based risk factors fall short in predicting near-future events in a high-risk individual. In the early 2000s, the focus of research into surrogate markers for cardiovascular event prediction shifted from the vulnerable plaque to the identification of the vulnerable patient.This new paradigm stimulated a number of new initiatives that aimed to identify vulnerable patients by testing systemic biomarkers that could identify patients at high risk for cardiovascular events. A second research paradigm is refocusing on the plaque by searching for plaque-derived biomarkers and non-invasive imaging modalities to assess characteristics of a plaque that determine its vulnerability.Although both concepts are attractive, they still need proper validation in large multicenter cohorts, while cost-effectiveness arguments also need to be assessed.
Keywords: Cardiovascular event prediction; imaging; risk factors; biomarkers; atherosclerosis